Generation of EMIC Waves and Effects on Particle Precipitation During a Solar Wind Pressure Intensification With Bz>0. Issue 6 (29th June 2019) - Lessard, Marc R.; Paulson, Kristoff; Spence, Harlan E.; Weaver, Carol; Engebretson, Mark J.; Millan, Robyn; Woodger, Leslie; Halford, Alexa; Horne, Richard; Rodger, Craig J.; Hendry, Aaron
Abstract: During geomagnetic storms, some fraction of the solar wind energy is coupled via reconnection at the dayside magnetopause, a process that requires a southward interplanetary magnetic field B z . Through a complex sequence of events, some of this energy ultimately drives the generation of electromagnetic ion cyclotron (EMIC) waves, which can then scatter energetic electrons and ions from the radiation belts. In the event described in this paper, the interplanetary magnetic field remained northward throughout the event, a condition unfavorable for solar wind energy coupling through low‐latitude reconnection. While this resulted in SYM/H remaining positive throughout the event (so this may not be considered a storm, in spite of the very high solar wind densities), pressure fluctuations were directly transferred into and then propagated throughout the magnetosphere, generating EMIC waves on global scales. The generation mechanism presumably involved the development of temperature anisotropies via perpendicular pressure perturbations, as evidenced by strong correlations between the pressure variations and the intensifications of the waves globally. Electron precipitation was recorded by the Balloon Array for RBSP Relativistic Electron Losses balloons, although it did not have the same widespread signatures as the waves and, in fact, appears to have been quite patchy in character. Observations from Van Allen Probe A satellite (at postmidnight local time) showed clear butterfly distributions, and it may be possible that the EMIC waves contributed to the development of these distribution functions. Ion precipitation was also recorded by the Polar‐orbiting Operational Environmental Satellite satellites, though tended to be confined to the dawn‐dusk meridians. Key Points: Solar wind pressure fluctuations were directly transferred to the magnetosphere and then propagated throughout the magnetosphere Global pressure perturbations provided temperature anisotropies that drove EMIC waves throughout the magnetosphere Electron precipitation was recorded by the BARREL balloons, although it did not have the same widespread signatures as the wave signatures